Explaining BUMDes Success: The Role of Managerial Capability and Community Participation in Rural Enterprises - Arik Prasetya; Irfan Kharisma Putra; Ahmad Bachtiar Arif; Layyin Nafisa (Universitas Negeri Surabaya, 2026)
This study examines the influence of managerial capability and community participation on the success of Village-Owned Enterprises (BUMDes) in Wonosalam District, Jombang Regency, Indonesia. BUMDes are expected to serve as key drivers of rural economic development through the management of local potential; however, their performance remains uneven across regions. This study adopts a mixed-method approach, combining quantitative analysis using multiple linear regression with qualitative insights from in-depth interviews. Data were collected from 96 respondents representing various BUMDes. The findings indicate that managerial capability has a significant positive effect on BUMDes success, particularly in planning, decision-making, and financial management. Community participation also demonstrates a significant positive influence, as involvement in planning and program evaluation strengthens community ownership and social support. Furthermore, the combined effect of managerial capability and community participation reveals a synergistic relationship that enhances BUMDes effectiveness and sustainability. This study contributes to the rural enterprise literature by highlighting the complementary roles of managerial competence and participatory governance. Practically, the findings emphasize the need to strengthen managerial capacity and institutionalize inclusive community engagement to support sustainable BUMDes development.